Research progress on negative electrodes for practical li-ion batteries : beyond carbonaceous anodes - Aravindan, Vanchiappan (2015)
Research activities related to the development of negative electrodes for construction of high-performance Li-ion batteries (LIBs) with conventional cathodes such as LiCoO2, LiFePO4, and LiMn2O4 are described. The anode materials are classified in to three main categories, insertion, conversion, and alloying type, based on their reactivity with Li. Although numerous materials have been proposed (i.e., for half-cell assembly), few of them have reached commercial applications, apart from graphite, Li4Ti5O12, Si, and Sn-Co-C. This clearly demonstrates that full-cell studies are desperately needed rather than just characterizing materials in half-cell assemblies. Additionally, the performance of such anodes in practical Li-ion configurations (full-cell) is much more important than merely proposing materials for LIBs. Irreversible capacity loss, huge volume variation, unstable solid electrolyte interface layer formation, and poor cycleability are the main issues for conversion and alloy type anodes. This review addresses how best to circumvent the mentioned issues during the construction of Li-ion cells and the future prospects of such anodes are described in detail.